Unconditional Love of Jojo Moyes’s Novel Me Before You - Nasution, Shery Syahira; Chitra, Bima Phrana (ANFA MEDIATAMA, 2023)
Unconditional love is often discussed in literature, specially novels. According to the explanation. In general, love process will produce unconditional love. As what Fromm (2019:5) confirms that: “Love is a power which produces love; impotence is the inability to produce love. ” . Unconditional love can be seen clearly, especially in Louissa Clark in Jojo Moyes’ novel Me Before You. To find the meaning of unconditional love in literature, it is necessary to introduce theory in the form of structuralism. This research uses qualitative method. The purpose of this study is to know the types and function of unconditional love in this novel.